Necrotizing Enterocolitis Incidence, Characteristics, and Outcomes in Neonatal Down Syndrome Patients - Cua, Clifford L.; Haque, Urbee; Miao, Yongjie; Backes, Carl H. (American Journal of Perinatology, 2017)
Introduction Neonates with Down syndrome (nDS) have multiple medical issues that may place them at an increased risk of necrotizing enterocolitis (NEC). The goal of this study was to determine the incidence, characteristics, and outcomes of nDS patients that developed NEC.Methods Data from the Pediatric Health Information Systems database on all nDS were reviewed. Demographics, medical conditions, development of NEC, and mortality were recorded. Patients were divided into nDS patients who developed NEC (nDS-NEC) versus nDS patients who did not develop NEC (nDS-nNEC).Results Incidence of NEC in nDS patients was 6.6% (381/5,737). Baseline demographic data indicated nDS-NEC patients were more likely to be born earlier, have a diagnosis of congenital diaphragmatic hernia, ventricular septal defect, patent ductus arteriosus, Ebstein's anomaly, or a left-sided obstructive lesion versus nDS-nNEC patients. The odds ratio for death in the nDS-NEC patients was 2.5 (95% confidence interval, 1.8–3.3) versus the nDS-NEC patients.Conclusion The incidence of NEC in nDS patients requiring admission to a children's hospital after birth is much higher than that reported for term infants. Baseline characteristics differ in nDS patients that may place them at a higher risk for NEC. nDS-NEC patients have an increased morbidity and a significantly higher mortality compared with the nDS-nNEC patients.
Keywords: necrotizing enterocolitis; Down syndrome; neonatal